Peningkatan Kesadaran Tentang Edukasi Mencegah dan Mendeteksi Stroke Secara Dini Pada Masyarakat: Penelitian - Edy Riawan; Zaikar Faizal; Aas Hasda Malida; Yenni Afriyani; Vera Feriska; Alimah; Aang Siswanto; Agung Kurnia Gravidoni; Anis Ayu Wijayanti; Ayu Rizki Wardani; Ahmad Rasyid Muttaqin; Begin Widodo; Budi Setyo Utomo; David Pranata; Edita Izni Fauziah; Eli Herawati; Febry Dio Saputra; Ika Insafuri; Linda Mulyana; Mauly Dinda Saputri; Mawar Indah Sari; Muhammad Gefaldo Dorisman; Nadia Sartika; Prana Citra; Radika Dirgantara; Rendi Pratama Saputra; Sigit Sugiarto; Tri Sundari; Tubagus Santri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Stroke is one of the leading causes of death and disability worldwide, affecting quality of life, daily activities, and both physical and psychological health. Prevention and early detection of stroke are crucial to reduce the risk of complications and long-term disability. This study aimed to increase community awareness about stroke prevention and early detection through an educational program at Puskesmas Rawat Inap Mampu PONED Kibang Budi Jaya on September 28, 2025. The method used was an educational and participatory approach, including pretest-posttest assessments, interactive health education, demonstrations of early stroke detection using the FAST (Face, Arm, Speech, Time) method, and discussion with practical simulations. The results showed a significant improvement in community knowledge, with an average increase of 50% in understanding stroke, recognizing its symptoms, and first aid measures. Before the intervention, only 25–40% of participants knew the correct first aid steps, which increased to 80–85% after the educational program. These findings indicate that interactive health education supported by educational media effectively enhances the community's ability to recognize stroke symptoms and respond with timely and appropriate first aid. This program can serve as a model for community-based interventions for primary prevention and early detection of stroke.